Molecular and Electronic Structure of ä-Valerothiolactone - Dugarte Jiménez, Nahir Yerely (2010)
The crystal structure of the six-member heterocyclic δ-valerothiolactone (1-thiocycloalkan-2-one) compound has been determined by X-ray diffraction at low temperature, revealing that its skeleton adopts a half-chair conformation. The conformation around the thioester group is almost planar with an anti orientation of the C═O double bond with respect the S−C single bond [C(2)−S(1)−C(6)−O(1) = 176.26(8)°]. The skeletal parameters, especially valence angles [∠C5−C6−S = 121.19(6)°, ∠O═C6−C5 = 122.25(8)°, ∠C6−S−C2 = 106.80(4)°], differ from those typically found in acyclic thioester compounds, symptomatic of the presence of strain effects. The conventional ring strain energy was determined to be 7.5 kcal/mol at the MP2/6-311++G(d,p) level of calculation within the hyperhomodesmotic model approximation. Moreover, the valence electronic structure was investigated by HeI photoelectron spectroscopy assisted by quantum chemical calculations at the OVGF/6-311++G(d,p) level of theory. The first three bands at 9.35, 9.50, and 11.53 eV denote ionizations related with the nS, nO, and πC═O orbitals, respectively, demonstrating the importance of the −SC(O)− group in the outermost electronic properties.